Effect of supplementation with barley and calcium hydroxide on intake of Mediterranean shrubs by goats - Rogosic, Jozo; Saric, Tomislav; Herceg, Nevenko; Zjalic, Slaven; Stanic, Svjetlana; Skobic, Dragan (ITALIAN JOURNAL OF ANIMAL SCIENCE, 2011)
Maquis plant communities are one of the most varied vegetation types in the Mediterranean region and an important habitat for wild and domestic herbivores. Although the majority of these shrubs are nutritious, the secondary compounds are the main impediments that reduce their forage value. In five experiments, we determined the effect of supplementing the diets of goats with calcium hydroxide plus barley and with barley alone on their intake of five dominant shrubs (Quercus ilex, Erica multiflora, Arbutus unedo, Viburnum tinus and Pistacia lentiscus) of the Mediterranean maquis community. The combination of calcium hydroxide plus barley and barley alone increased the utilisation of Q. ilex, E. multiflora and P. lentiscus, while the intake of A. unedo and V. tinus was not statistically significantly different. Calcium hydroxide and barley (energy) enhance the use of secondary compound-containing plants, which may increase the production of alternate forages and create a more diverse mix of plant species in the Mediterranean maquis plant community.
The following values have no corresponding Zotero field: pub-location: MEDITGROUP, VIA G BELLI, 4, PAVIA, 27100, ITALY publisher: PAGEPRESS PUBL
Keywords: barley; Calcium hydroxide; Food preference; Goat; Secondary compound

Influence of secondary compound complementarity and species diversity on consumption of Mediterranean shrubs by sheep - Rogosic, Jozo; Estell, Richard E.; Skobic, Dragan; Stanic, Svjetlana (Applied Animal Behaviour Science, 2007)
Generalist herbivores foraging in chemically diverse grazing ecosystems like the Mediterranean maquis increase intake on mixed diets, suggesting they are more able to meet nutritional needs and avoid toxicosis. Thus, our objectives were to determine how shrub species diversity and complementary interactions between tannins and saponins inﬂuence intake of Mediterranean shrubs by sheep. We conducted four experiments (10 days each) comparing intake of mixtures of Mediterranean shrubs varying in number of species and/or principal class of secondary compound (tannins or saponins) by sheep (n = 12). Sheep consumed more total foliage (P < 0.01) when offered a high-tannin shrub (Pistacia lentiscus; Exp. 1), two high-tannin shrubs (P. lentiscus and Arbutus unedo; Exp. 2), or three high-tannin shrubs (P. lentiscus, A. unedo, and Quercus ilex; Exp. 3) when fed in conjunction with a high-saponin shrub (Hedera helix) than with an equal number of high-tannin shrubs (20.9 g/kg BW versus 16.3 g/kg BW; 28.8 g/kg BW versus 20.8 g/kg BW; and 35.3 g/kg BW versus 26.9 g/kg BW). Likewise, sheep ate more foliage (P < 0.01) of each additional individual shrub (P. lentiscus, A. unedo, and Q. ilex) in the mixture when fed with H. helix than with an equal number of high-tannin shrubs (8.2 g/kg BW versus 5.0 g/kg BW; 13.3 g/kg BW versus 10.7 g/kg BW; and 7.6 g/kg BW versus 5.2 g/kg BW; Exps. 1–3, respectively), suggesting a complementary interaction between tannins and saponins may have occurred. Sheep also appeared to increase total shrub intake as number of shrub species on offer increased, regardless of number of classes of compounds present. Our ﬁndings suggest that secondary compounds in Mediterranean shrubs (tannins and saponins) are complementary. Species diversity also plays an important role in diet selection, as plant species with different types and amounts of nutrients and phytotoxins may affect forage intake and animal production. This knowledge will help livestock producers to capitalize on phytochemical interactions to enhance intake, optimize forage utilization, and ultimately improve performance of browsing ruminant herbivores
Keywords: Biodiversity; Complementarity; Mediterranean maquis; Saponins; Secondary compounds; Sheep; Shrubs; Tannins

Influence of secondary compound complementarity and species diversity on consumption of Mediterranean shrubs by sheep - Rogosic, Jozo; Estell, Richard E; Skobic, Dragan; Stanic, Svjetlana (Applied Animal Behaviour Science, 2007)
Generalist herbivores foraging in chemically diverse grazing ecosystems like the Mediterranean maquis increase intake on mixed diets, suggesting they are more able to meet nutritional needs and avoid toxicosis. Thus, our objectives were to determine how shrub species diversity and complementary interactions between tannins and saponins inﬂuence intake of Mediterranean shrubs by sheep. We conducted four experiments (10 days each) comparing intake of mixtures of Mediterranean shrubs varying in number of species and/or principal class of secondary compound (tannins or saponins) by sheep (n = 12). Sheep consumed more total foliage (P < 0.01) when offered a high-tannin shrub (Pistacia lentiscus; Exp. 1), two high-tannin shrubs (P. lentiscus and Arbutus unedo; Exp. 2), or three high-tannin shrubs (P. lentiscus, A. unedo, and Quercus ilex; Exp. 3) when fed in conjunction with a high-saponin shrub (Hedera helix) than with an equal number of high-tannin shrubs (20.9 g/kg BW versus 16.3 g/kg BW; 28.8 g/kg BW versus 20.8 g/kg BW; and 35.3 g/kg BW versus 26.9 g/kg BW). Likewise, sheep ate more foliage (P < 0.01) of each additional individual shrub (P. lentiscus, A. unedo, and Q. ilex) in the mixture when fed with H. helix than with an equal number of high-tannin shrubs (8.2 g/kg BW versus 5.0 g/kg BW; 13.3 g/kg BW versus 10.7 g/kg BW; and 7.6 g/kg BW versus 5.2 g/kg BW; Exps. 1–3, respectively), suggesting a complementary interaction between tannins and saponins may have occurred. Sheep also appeared to increase total shrub intake as number of shrub species on offer increased, regardless of number of classes of compounds present. Our ﬁndings suggest that secondary compounds in Mediterranean shrubs (tannins and saponins) are complementary. Species diversity also plays an important role in diet selection, as plant species with different types and amounts of nutrients and phytotoxins may affect forage intake and animal production. This knowledge will help livestock producers to capitalize on phytochemical interactions to enhance intake, optimize forage utilization, and ultimately improve performance of browsing ruminant herbivores
Keywords: Biodiversity; Complementarity; Mediterranean maquis; Saponins; Secondary compounds; Sheep; Shrubs; Tannins